Роль использования современных инновационных и педагогических технологий при изучении английского и русского языка в техническом вузе - Хазраткулова А (Periodica Journal, 2022)
Тhis article discusses the questions concerning the use of modern information and pedagogical technologies and their role in learning foreign languages successfully.
Keywords: Information; technologies; methods; communicative